Penerapan Ketentuan dalam Praktik Sita Jaminan Atas Saham guna Memperoleh Kepastian Hukum - Adelia Audiana Gerchikova (Journal of Judicial Review, 2020)
This research is intended to assert the legal basis for Shares Guarantee Seizure implementation, and execution mechanism towards Court Judgement of Permanent Legal Force, based on positive laws, which should be enforced as an actual legal basis in order to achieve legal certainty as a practice of Shares Guarantee Seizure implementation. The research is conducted through normative juridical method approach with descriptive analytical research specifications, and data analysis performed with qualitative methods. This study results shown, firstly, the actual legal basis for the efforts of Shares Guarantee Seizure is contained in article 227 section (1) of HIR in conjunction with Article 511 of The Indonesian Civil Code, as long as its implementation fulfills the basic requirements. Therefore, the Judges are forbidden to refer to Book II of Technical Guidelines for Administrative and Practical Civil Justice as a basis of legal considerations in their verdict, given that these guidelines are not the product regulation. Secondly, there are several distinct in the execution mechanisms of Shares Guarantee Seizure towards limited companies, concludes that Guarantee Seizure of a private company stock is merely administrative by way a Bailiff registered the stock identity in Department of Law and Human Rights (Depkumham), that no obstacles were encountered in performing the execution. While shares guarantee seizure execution of a public company is way too difficult because it is hard to identify respective stocks on Stock Market. Juridically speaking, the stock is happened to be seized, but the execution is not possible to comply. Both mechanisms have not been asserted in HIR, therefore the rule itself became unclear, whereas rules supposed to achieve legal certainty. Hence, to obtain legal certainty, new product regulations for Procedure of Civil Law are required in legislation (wet) arrangement, which should accommodate most of legal issues dynamics in Indonesia.